Whippoorwill - Monninger, Joseph (Houghton Mifflin Harcourt, 2015)
In rural New Hampshire, sixteen-year-old Clair Taylor and her neighbor, eighteen-year-old Danny Stewart, fall into an unlikely relationship as they work together to save Wally, a lovable but mistreated dog kept chained in a junk-filled yard by Danny's cruel father.